A novel approach for hazardous area identification of toxic gas leakage accidents on offshore facilities. (1st December 2020) - Yang, Dongdong; Chen, Guoming; Shi, Jihao; Zhu, Yuan; Dai, Ziliang
Abstract: Some attempts have been made to predict the adverse effects of released toxic gas on individuals. However, the classification of the hazardous area considering the dynamic changes and focusing on the whole facility remains a challenging issue. This paper presents a novel approach to classify the hazardous areas on offshore facilities in toxic gas leakage and dispersion accident. By introducing the grid-based concept, each location and its corresponding evacuation trajectory to a fixed destination are considered in this approach. Instead of just considering the accumulation characteristics of released toxic gas, the adverse effects are predicted with a combination of the dynamic factors, including the emergency evacuation and the temporal-spatial variation of toxic gas profile. The proposed approach is applied to a hypothetical H2 S leakage and dispersion accident on an offshore platform, a time-varying leakage profile is adopted considering the interference of the process protection measures, an emergency evacuation time model is established with the guideline from International Maritime Organization (IMO). The results suggest that the proposed approach can improve the accuracy of hazardous areas identification and provide support for optimizing emergency plans against toxic gas leakage and dispersion accident on offshore facilities. Highlights: The whole facility is of interest instead of just focusing on the areas with high concentration toxic gas. An emergency evacuation time model is established, and the emergency evacuation of the individuals is considered. A time-varying leakage rate is adopted considering the interference of the emergency shutdown system and blowdown system. The adverse effects are calculated by considering the variation of the toxic gas profile and individuals' position.